1973
DOI: 10.1007/bf01408067
|View full text |Cite
|
Sign up to set email alerts
|

(p, t) Reaction studies on some even isotopes of samarium

Abstract: The (p, t) reaction on the even isotopes 144Sm, 148Sm and 15~ has been investigated at an incident proton energy of 25.5 MeV. Angular distributions have been measured for transitions to the ground state and excited states up to an excitation energy of about 2.5 MeV. Especially the L=0 angular distributions are discussed.The isotopes of samarium (Z= 62) seem to be very interesting for the investigation with two-neutron transfer reactions, since they cover a range from a closed neutron shell nucleus (144Sm, N= 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In 1973 Oelert' performed (P, t) reaction studies on samarium isotopes and reported levels in ' 'Sm at 0 (0 ), 768+15 (2'), 1785+15 (4'), 2040+20 (2'), and 2358*20 keV.…”
Section: Introductionmentioning
confidence: 99%
“…In 1973 Oelert' performed (P, t) reaction studies on samarium isotopes and reported levels in ' 'Sm at 0 (0 ), 768+15 (2'), 1785+15 (4'), 2040+20 (2'), and 2358*20 keV.…”
Section: Introductionmentioning
confidence: 99%